2015
DOI: 10.1016/j.repc.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement for severe aortic stenosis in octogenarians: Patient outcomes and comparison of operative risk scores

Abstract: These results suggest that AVR can be performed safely in selected octogenarians. EuroSCORE II and STS demonstrated superior calibration and should be the preferred tools for risk assessment, at least for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…[7][8][9] Other studies showed lower mortality rates in octogenarians with CAD and aortic valve stenosis, but only stated perioperative, no 30-day mortality rates. 10 In a population of octogenarians at low operative risk (STS (Society of Thoracic Surgeons) score: 3.2%), Krishna et al 11 reported a low 30-day mortality (3.1%) with a minimally invasive approach to AVR. In a retrospective, but propensityscore matched analysis, minimally invasive AVR was not shown to be superior to standard AVR.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Other studies showed lower mortality rates in octogenarians with CAD and aortic valve stenosis, but only stated perioperative, no 30-day mortality rates. 10 In a population of octogenarians at low operative risk (STS (Society of Thoracic Surgeons) score: 3.2%), Krishna et al 11 reported a low 30-day mortality (3.1%) with a minimally invasive approach to AVR. In a retrospective, but propensityscore matched analysis, minimally invasive AVR was not shown to be superior to standard AVR.…”
Section: Discussionmentioning
confidence: 99%
“…They contained a heterogenous mix of patients, procedures and locations, commonly found in these studies [6,22,23]. Twenty studies reported on all operations performed [2, [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], 11 reported on aortic valve replacements with or without coronary artery bypass grafts (CABG) [43][44][45][46][47][48][49][50][51][52][53], 8 CABG only [54][55][56][57][58][59][60][61], 2 on mitral valve repair/replacement [62,63], 2 on unspecified valvular operations [64,65] and 1 on thoracic aortic [66] operations. A total of 23 were based in Europe [2, 24, 25, 28, 31, 35-39, 42, 46, 48-50, 53-57, 59, 62, 67], 5 in North America (NA)…”
Section: Study Characteristicsmentioning
confidence: 99%
“…La mortalité observée à 30 jours de l'intervention est proche de celle prédite par l'EUROSCORE II. Sa prédiction est meilleure que celle de l'EUROSCORE I, qui surestime grandement le risque de mortalité opératoire, et légèrement inférieure à celle du STS score 25,26 . Cependant, sa spécificité est critiquée pour les pathologies valvulaires 27 .…”
Section: Introductionunclassified